The Effect of Applying the Storytelling Method to Improve Speaking Skills in Early Childhood - Maulani, Choirul; Yuniarti, Yuniarti; Sutrisno, Sutrisno (Perkumpulan Peneliti Pendidikan dan Pengembangan Anak, 2025)
Childhood at RA Mas'Udi Pontianak Kota are still low at 40%, this is indicated by children who have not been able to answer questions given by the teacher and children have not been able to do what the teacher ordered. Therefore, this study aims to determine the effect of the storytelling method on children's speaking skills. The research method used in this study is an experimental method with a quantitative approach. The research sample was children of RA Mas'Udi Pontianak Kota totaling 6 children consisting of 2 boys and 4 girls. Data collection techniques using observation and tests. Data analysis test using Paired Sample T-Test test obtained Sig (2-tailed) value of 0.000 <0.05, which means Ha is accepted and Ho is rejected. The results showed that there was an increase in children's speaking skills can be seen in the results of the research obtained in the pre-test results before the treatment was 3.83% and the post-test value after treatment was 9.83%. So it can be concluded that there is an effect of the application of the storytelling method on improving the speaking skills of early childhood at RA Mas'Udi Pontianak Kota.